Ethnography in Congregations - Anna Mitchell Hall (Adult Education Research Conference, 2013)
Ethnography is increasingly used in research conducted in congregations. Ethnography can provide rich description and is able to navigate between the stories of congregational members and the story observed by the researcher. Quality ethnography in congregations requires attention to ethics, navigating insider/outsider dynamics, and research aims.